Integrated Laboratory-Based Learning in Pesantren: A Community Service Initiative at Darul Faqih Islamic Boarding School - Nurul Hidayat; Arif Hidayat; Ahmad Taufiq; Edi Supriana; ST Ulfawanti Intan Subadra; Lya Rizka Herawati; Erni Yulianti (GUYUB: Journal of Community Engagement, 2025)
Pesantren play a crucial role in shaping a young generation with transdisciplinary capabilities by integrating religious and scientific knowledge. In Islamic boarding schools, science education requires curriculum integration through laboratory-based learning. This community service program was conducted at Pondok Pesantren Darul Faqih, Malang, aiming to improve laboratory facilities and enhance teachers’ competence in facilitating experiment-based learning. This program involved providing laboratory equipment and teacher training using lecture and practice methods. Three main stages were carried out: (1) providing basic experimental equipment for an integrated laboratory, (2) conducting seminars on Islamic-based practical management and mentoring teachers in developing science experiment modules, and (3) implementing experiments and evaluating the program. A questionnaire was distributed to teachers to assess their views on the importance of laboratories in science education. The results showed an improvement in laboratory facilities with the availability of various experimental tools, such as the Melde Kit, Hooke’s Law Kit, Kirchhoff’s Law Kit, and Solar Cell Kit. Additionally, the training enhanced teachers' skills in operating the equipment and developing science learning modules. According to the survey, the equipped laboratory contributed to increased student motivation and understanding of science. This program is expected to serve as a model for advancing science education in pesantren